Dutch Discrimination Against The Natives in Film Bumi Manusia (Study of Discourse Analysis Teun A.Van Dijk) - Ihza Mahendra; Ahmad Tamrin Sikumbang; Suheri Harahap (Pena Cendekia Insani, 2023)
Film is a communication medium that combines two elements, namely audio (sound) and visual (image) which functions to convey a message to individuals or the general public who gather in a certain place. Film has so many meanings depending on the point of view of the researchers, in my opinion film is one of the mass communication media that displays a series of moving images with a storyline played by actors who have been produced by producers to convey a message to the audience. This study aims to find out the forms of discrimination against natives in the film Bumi Manusia based on Teun A. Van Dijk's discourse analysis by analyzing discriminate texts. This study uses a qualitative approach with Teun A Van Djik's critical discourse analysis as the motive. The data collection technique in this study is that researchers will carry out literature study techniques and note taking techniques. The data analysis technique was adapted to Teun A. Van Djik's discourse analysis, namely text and social context analysis. This research resulted in the conclusion that the film Bumi Manusia shows social discrimination through social status, education, laws that were in force at that time, and discrimination against women. The social context shows that the discrimination that occurred in the film Bumi manusia during the colonial era of the 1920s is still relevant to Indonesia's current situation.